Dust mites as occupational allergens in two bakeries of La Habana, Cuba - Bárbara I Fernández-Duro; Mirta Álvarez-Castelló; Mayteé Mateo-Morejón; Bárbara Luis-Rodríguez; Alexis Labrada-Rosado (Revista Alergia México, 2014)
Background: Occupational allergies are becoming more frequent. The allergens present in the working environment of bakeries, such as mites, are not well identified despite being known risk factors of respiratory diseases.